Functional Properties of Nd:YAG Polycrystalline Ceramics Processed by High‐Pressure Spark Plasma Sintering (HPSPS). Issue 3 (12th December 2015) - Sokol, Maxim; Kalabukhov, Sergey; Kasiyan, Vladimir; Dariel, Moshe P.; Frage, Nachum
Abstract : High‐pressure spark plasma sintering (HPSPS) was employed to fabricate polycrystalline Nd:YAG specimens with desired functional properties. Specimens fabricated under a uniaxial pressure of 300 MPa at 1300°C at a heating rate of 50°C/min and holding time of 60 min displayed submicrometer microstructure and elevated mechanical properties, including resistance to thermal shock. Optical properties (i.e., spectral transmittance, fluorescence emission spectra and fluorescence lifetime) of the HPSPS‐processed specimens were close to those obtained with specimens fabricated by conventional sintering procedure. Specifically, remarkable differences in threshold power and laser slope efficiency were found and attributed to the variance in Nd concentration in the specimens tested. The results of this study indicate that the low cost and timesaving HPSPS process allows for the fabrication of polycrystalline Nd:YAG specimens with optical properties suitable for laser applications.